Impact of Omnichannel Retailing on Customers’ Purchase Decision Journey in the Consumer Goods Sector: A Case of the Beauty Care Category in Vietnam - Phuong Thuc, Le Huynh (Digital Repository of Theses - SSBM Geneva, 2024)
Aim: This research aimed to examine the impact of omnichannel retailing on customers’ purchase intention in the beauty care category within the Vietnam market. The impact of omnichannel retailing would be measured through the integration level defined by connectivity and consistency of the retail elements over customers’ purchase intention. By employing a mixed-methods approach, the study sought to identify the impact of integration levels and the key retail mix elements, understand the significance, and analyze the relationships with customers’ purchase intention. Method: The study adopted a two-phase approach. In the qualitative phase, face-to-face interviews were conducted with omnichannel experts to identify and comprehend the essential omnichannel retail mix elements that impact omnichannel purchase decisions. Subsequently, the quantitative phase employed surveys to examine the integration levels, connectivity, and consistency scores, additionally analyzing the relationships between the defined essential omnichannel retail mix elements and customers' purchase intention. Findings: The study revealed that the degree of integration, specifically measured by connectivity and consistency, played a critical role in influencing customers’ purchase intention. Connectivity was identified as having a higher impact than consistency. Varying levels of integration among retailers in the Vietnam market were discovered, emphasizing the need for tailored omnichannel strategies. Furthermore, five out of ten examined retail mix elements exhibited a significant positive impact on purchase intention including product uniqueness, product information, price transparency, personalization service, and post- purchase support. Value: This research provided valuable insights and practical guidance for retailers aiming to accelerate the omnichannel strategy in Vietnam's beauty care sector. The confirmed impact of integration levels through connectivity and consistency as well as the identified significant retail mix elements offered retailers guidance to create a measurable impact on customers’ purchase intention. The finding lists and implications served as a valuable framework for retailers in prioritizing areas for improvements. The study's findings contributed to the broader academic understanding of omnichannel retailing and emphasized the importance of strategic omnichannel integration investment and a customer-centric approach. Additionally, the research suggested recommendations for future explorations, providing a foundation for further studies in the dynamic landscape of omnichannel retailing, especially in the context of emerging markets such as Vietnam.